2008
DOI: 10.1080/11250000801931753
|View full text |Cite
|
Sign up to set email alerts
|

The salinity tolerance ofPseudophoxinus stymphalicus(Cyprinidae) andValencia letourneuxi(Valenciidae) from western Greece suggests a revision of the ecological categories of freshwater fishes

Abstract: The salinity tolerance of two common teleosts from Greece, one a primary division species, Pseudophoxinus stymphalicus, the other a secondary division species, Valencia letourneuxi, was evaluated in laboratory studies. Experimental subjects were acclimated to a salinity of 6 ppt. Through gradual increases, individuals of P. stymphalicus were able to tolerate salinities up to 12-13 ppt, while individuals of V. letourneuxi survived in normal seawater (33 ppt) and had an upper lethal limit of ca. 46 ppt. Valencia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 24 publications
1
23
0
Order By: Relevance
“…Three species have been described in this region which belong to the Padano‐Venetian district: Salmo farioides Karaman, ; from the Krka River and several others rivers, described before as Salmo zrmanjaensis Karaman, ; from the Zrmanje River (Karaman, ), and Salmo visovacensis Taler, 1850 from the Visovacic Lake and Krka River. These basins include numerous primary or primary‐like representatives (Bianco and Nordlie, ) of the Padany‐Venetian district: Padogobius bonellii , Alburnus arborella , Squalius squalus , Pomatoschistus canestrini , and Barbus plebejus . Also, for palaeogeographic history, dispersal events occurred during the last Würm glaciation, about 10–15 000 years ago, when the extended Po basin reached the meso‐Adriatic ditch in the central Adriatic Sea (Bianco, ), joining rivers of the two Adriatic slopes.…”
Section: Resultsmentioning
confidence: 97%
“…Three species have been described in this region which belong to the Padano‐Venetian district: Salmo farioides Karaman, ; from the Krka River and several others rivers, described before as Salmo zrmanjaensis Karaman, ; from the Zrmanje River (Karaman, ), and Salmo visovacensis Taler, 1850 from the Visovacic Lake and Krka River. These basins include numerous primary or primary‐like representatives (Bianco and Nordlie, ) of the Padany‐Venetian district: Padogobius bonellii , Alburnus arborella , Squalius squalus , Pomatoschistus canestrini , and Barbus plebejus . Also, for palaeogeographic history, dispersal events occurred during the last Würm glaciation, about 10–15 000 years ago, when the extended Po basin reached the meso‐Adriatic ditch in the central Adriatic Sea (Bianco, ), joining rivers of the two Adriatic slopes.…”
Section: Resultsmentioning
confidence: 97%
“…The 96 hr LC 50 value of salinity were recorded in several studies, such as 6‰ for Aristichthys nobilis (Garcia, Garcia, Pineda, Gammad, & Canta, 1999), 11‰ for Pseudophoxinus stymphalicus (Bianco & Nordlie, 2008) and 13‰ for Jaba barb (Amin et al, 2016). Fish species respond differently at different salinity levels.…”
Section: Discussionmentioning
confidence: 99%
“…Conductivity which corresponds to salinity, was not apparently negatively related to the presence of V. letourneuxi, as the species was found also in three habitats with brackish water (Northern Acheron canal, Vlychos springs and Astakos springs) indicating its tolerance to higher saline conditions. A recent study has shown that V. letourneuxi is indeed one of the least salinity tolerant species in comparison with other secondary division species, with a primarylike distribution in the Mediterranean area (Bianco & Nordlie 2008). …”
Section: Aspects Of Ecologymentioning
confidence: 99%